Equity and Social Justice in Research Practice Partnerships in the United States. (October 2022) - Vetter, Amy; Faircloth, Beverly S.; Hewitt, Kimberly K.; Gonzalez, Laura M.; He, Ye; Rock, Marcia L.
Research–practice partnerships (RPPs) have grown rapidly in the last decade in the United States to challenge traditional notions of education research by emphasizing the importance of researchers and practitioners working together in a spirit of mutuality to develop research questions, collect data, implement interventions, and analyze and use findings. RPP scholarship in the United States has historically advocated for the need to pay more focused attention to issues of equity and justice. To address that need, this literature review examined how RPPs in the United States have addressed equity and justice in their work. Based on five dimensions of equity and justice that could be observed within the 149 examples of RPP work we reviewed, we identified 17 exemplar projects that explicitly and effectively forefront equity and justice in RPPs, what we call equity-focused. Implications suggest that researchers and practitioners who have initiated equity-orientated RPPs may reflect on the partnerships' existing strengths, specifically related to the five interconnected features that characterize equity-focused RPPs, to sustain and advance equity and justice through RPPs.